Effects of stimulus presentation order during auditory–visual conditional discrimination training for children with autism spectrum disorder. Issue 2 (14th December 2018) - Cubicciotti, Julie E.; Vladescu, Jason C.; Reeve, Kenneth F.; Carroll, Regina A.; Schnell, Lauren K.
Abstract : Children with autism spectrum disorder are typically taught conditional discriminations using a match‐to‐sample arrangement. Consideration should be given to the temporal order in which antecedent stimuli (the sample and comparison stimuli) are presented during match‐to‐sample trials, as various arrangements have been used in the extant literature. The purpose of the current study was to compare the effects of four stimulus presentation orders on the acquisition of auditory–visual conditional discriminations. The study included participants from a clinically relevant population (three children with autism spectrum disorder), employed clinically relevant teaching procedures, and included two presentation formats not included in previous comparison evaluations (simultaneous and sample‐first with re‐presentation conditions). Results were found to be learner‐specific; that is, a different stimulus presentation format was most efficient for each participant. We provide suggestions to evaluate stimulus control topographies and enhance experimental control in match‐to‐sample arrangements.